2003
DOI: 10.1042/bj20021418
|View full text |Cite
|
Sign up to set email alerts
|

Formation of active monomers from tetrameric human beta-tryptase

Abstract: Tryptase is a serine protease that is stored at low pH in the mast cell secretory granules in complex with heparin proteoglycan. When mast cells are activated, e.g. during allergic responses, the tryptase/heparin complexes are released together with a variety of other preformed inflammatory mediators. Previous crystallization of human beta-tryptase revealed a unique tetrameric structure with all of the active sites facing a central pore that has a limited accessibility both for potential substrates as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
58
2
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 22 publications
5
58
2
1
Order By: Relevance
“…However, whether short heparin glycosaminoglycans are available to β-tryptase in vivo is uncertain. Formation of active monomers using recombinant human β-tryptase was also noted [74]. β-rTryptase (2 μg in 20 μl of 10 mM Mes, pH 6.1 containing 2 M NaCl) was diluted 10-fold in PBS, pH 7.4, and incubated at 37°C for 30 min.…”
Section: Tetramer ↔ Monomermentioning
confidence: 99%
“…However, whether short heparin glycosaminoglycans are available to β-tryptase in vivo is uncertain. Formation of active monomers using recombinant human β-tryptase was also noted [74]. β-rTryptase (2 μg in 20 μl of 10 mM Mes, pH 6.1 containing 2 M NaCl) was diluted 10-fold in PBS, pH 7.4, and incubated at 37°C for 30 min.…”
Section: Tetramer ↔ Monomermentioning
confidence: 99%
“…We have recently shown that human ␤-tryptase, when exposed to neutral pH and 37°C, can dissociate into heparin-dependent active monomers (23). We next wanted to test whether gelatin and type I collagen were substrates for both tryptase tetramers and monomers.…”
Section: Tryptase Degrades Gelatin and Denatured Type I Collagen In Smentioning
confidence: 99%
“…We next wanted to test whether gelatin and type I collagen were substrates for both tryptase tetramers and monomers. Tetrameric and (active) monomeric tryptase were isolated by size-exclusion gel chromatography using a running buffer containing heparin, as previously described (23). Gelatin or type I collagen was incubated (at room temperature and 37°C, respectively) with tetrameric or monomeric tryptase for different time periods, followed by SDS-PAGE analysis.…”
Section: Tryptase Degrades Gelatin and Denatured Type I Collagen In Smentioning
confidence: 99%
See 1 more Smart Citation
“…The ␤-tryptase tetramer is proteolytically active in both acidic and neutral pH buffers, though greater fibrinogenolytic activity occurs at acidic than neutral pH. In contrast, a heparin-stabilized monomeric form of mature ␤-tryptase has been detected at low concentrations of ␤-tryptase, which is inactive at neutral pH but active at acidic (pH 6 -6.5) conditions (22,40). High concentrations of ␤-tryptase monomers can be formed with the anti-␣␤-tryptase mAb, B12, as well as the B12 Fab fragment, which dissociates heparin-stabilized ␤-tryptase tetramers to monomers that, like free monomers, are inactive at neutral pH but active at acidic pH (23).…”
mentioning
confidence: 99%